Brain Drain Propensity for Malaysian Professionals to Leave for Singapore - Binti Jauhar, Junaimah; Abdul Ghani, Ahmad Bashawir; Islam, Rabiul; SpringerLink (Online service) (Singapore : Springer Singapore(Imprint), 2016)
This book focuses on skilled labour migration from Malaysia to Singapore. In this regard, it examines a number of variables such as Better Perks and Benefits, Quality of Work Life, Ease of Immigration Procedures, International Exposure, Greater Job Availability, and Social Networks, and how they influence the decisions of Malaysian accounting professionals. In doing so, the book elaborates on how this phenomenon is an indirect result of globalization, which is predominantly detrimental for developing countries such as Malaysia. The book also highlights the need for these experts in their home country, as Malaysia is currently striving to improve its economy in order to achieve high-income status by 2020.
Chapter 1: General Introduction -- Chapter 2: Malaysia's Development Policies -- Chapter 3: Literature Review -- Chapter 4: Research Methodology -- Data Analysis and Results -- Chapter 6: Discussion, Recommendations and Conclusions.
Keywords: Labor economics; Migration; Political economy; Emerging Markets/Globalization.